2019
DOI: 10.1002/pds.4933
|View full text |Cite
|
Sign up to set email alerts
|

Mapping from the International Classification of Diseases (ICD) 9th to 10th Revision for Research in Biologics and Biosimilars Using Administrative Healthcare Data

Abstract: Purpose: The Centers for Medicare and Medicaid Services (CMS) mandated the transition from ICD-9 to ICD-10 codes on October 1, 2015. Postmarketing surveillance of newly marketed drugs, including novel biologics and biosimilars, requires a robust approach to convert ICD-9 to ICD-10 codes for study variables. We examined three mapping methods for health conditions (HCs) of interest to the Biologics and Biosimilars Collective Intelligence Consortium (BBCIC) and compared their prevalence. Methods: Using CMS Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Our findings suggest that all studies using ICD‐9‐CM‐based algorithms mapped to ICD‐10‐CM codes should assess the performance of the mapping and undertake detailed reviews before using them. Although prior studies found that FBM may be generally more sensitive compared to SFM, 2,9‐11 our findings argue for careful review of all mapping approaches. Notably, a mapping method that is generally better than others may not be the best for all HOIs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our findings suggest that all studies using ICD‐9‐CM‐based algorithms mapped to ICD‐10‐CM codes should assess the performance of the mapping and undertake detailed reviews before using them. Although prior studies found that FBM may be generally more sensitive compared to SFM, 2,9‐11 our findings argue for careful review of all mapping approaches. Notably, a mapping method that is generally better than others may not be the best for all HOIs.…”
Section: Discussionmentioning
confidence: 52%
“…Mapping methods should be customized for individual studies and specific HOIs. Also, consistency in incidence and prevalence trends may be influenced by multiple factors, including parameters in study design, such as cohort re-entry conditions, length of wash-out period, care settings examined Furthermore, additional analyses of these reports would enhance our understanding of the value of manual code curation, as recommended by a prior study that reported manual refinement of a mapped ICD-10 algorithm of meningitis improved the consistency in prevalence, 11 and the best methods for assessing changes in incidence and prevalence across the ICD-9-CM and ICD-10-CM eras. A more in-depth analysis of the existing reports, or future reports, would include analysis of monthly incidence and prevalence data to allow more systematic assessment of changes in level and trend (i.e., beyond visual inspection) and investigation of whether manual curation can improve HOI phenotype performance as compared to prior trends.…”
Section: Discussionmentioning
confidence: 99%
“…Non-fatal CV event and death were prespecified secondary outcomes. We employed validated algorithms to identify non-fatal CV event using International Classification of Diseases ninth edition (ICD-9) diagnosis codes and procedural codes, updated to include corresponding ICD-10 codes 17–20. These algorithms defined MI, ACS and stroke using inpatient diagnosis codes.…”
Section: Methodsmentioning
confidence: 99%
“…Comorbidities previously associated with risk of CV disease or death, including diabetes, hypertension, hyperlipidaemia, atrial fibrillation and cancer, were defined by ≥2 ICD-9/10 codes from EHR entry through index date (see table 1 for a complete list of CV risk factors) 20. Requiring at least two ICD codes increases PPV for each comorbidity compared with one code; assessing comorbidities in all available data before index date is not expected to create bias 22 23.…”
Section: Methodsmentioning
confidence: 99%
“…This process involves translating ICD-9-CM codes to ICD-10-CM (forward-mapping), then translating the identified ICD-10-CM codes back to ICD-9-CM (backward-mapping) to capture codes that may not have one-to-one mapping between versions and to identify additional related codes that may be of relevance. Recent publications have reported that this approach is appropriate for efforts to define AMI using ICD codes [7,8]. The draft algorithm builds on these prior studies, using a more current version of the ICD-10-CM and an approach informed by high-quality ICD-9-CM validation studies, and was subject to further review and refinement by clinical subject matter experts.…”
Section: Literature Search and Algorithm Developmentmentioning
confidence: 99%